A Rare Case of Placental Lipoma in A Holstein Friesian Crossbred Cow - GHUMAN, S P S; HONPARKHE, M; SOOD, N K; GUPTA, K (The Indian Journal of Animal Reproduction, 2023)
A rare case of placental lipoma in a Holstein Friesian crossbred cow associated with fetal ascitci isreported.
Keywords: Ascites; Dystocia; Lipoma; Placenta